Clinical Significance of Polymorphisms in Immune Response Genes in Hepatitis C-Related Hepatocellular Carcinoma - De Re, Valli; Tornesello, Maria Lina; De Zorzi, Mariangela; Caggiari, Laura; Pezzuto, Francesca; Leone, Patrizia; Racanelli, Vito; Lauletta, Gianfranco; Gragnani, Laura; Buonadonna, Angela; Vaccher, Emanuela; Zignego, Anna Linda; et al. (Frontiers in Microbiology, 2019)
Background and aims Polymorphisms in the immune response genes can contribute to clearance of hepatitis C virus (HCV) infection but also mediate liver inflammation and cancer pathogenesis. This study aimed to investigate the association of polymorphisms in PD-1, IL28B and TLR2 immune genes in chronic HCV patients with different hepatic and lymphoproliferative HCV-related diseases. Methods Selected polymorphisms in these immune genes were tested by molecular approaches in 450 HCV-positive patients with hepatic diseases (including chronic infection, cirrhosis and hepatocellular carcinoma), 238 HCV-positive patients with a lymphoproliferative disease (cryoglobulinemia and non-Hodgkin lymphomas) and 94 blood donors. Results While IL28B T-allele variant was found a good marker associated with HCV-outcome together with TLR2 del variant, the PD-1.6 allele-A variant was found to have an insignificant role in patients with HCV-related hepatic disorders. Though in Asian the combination of IL28B and PD-1.6 markers better define the HCV-related outcomes, in our series of Caucasian patients the PD-1.6 allele-A variant was observed very rarely. Conclusion Differences in HCV-related hepatocellular carcinoma incidence and clinical response between Asian and European population were in part due to the distribution of PD-1.6 genotype that we found divergent between these two populations. Among the immune genes studied, only the IL28B and TLR2 variants remain significant markers associated with HCV-related diseases progression in our cohort of Italian patients.